Autoimmune reaction against pancreatic beta cells in children and adolescents with simple obesity - Chylińska-Frątczak, Aneta; Pietrzak, Iwona; Michalak, Arkadiusz; Wyka, Krystyna; Szadkowska, Agnieszka (Frontiers in Endocrinology, 2022)
Introduction One of the most important complications of obesity is insulin resistance, which leads to carbohydrate metabolism disorders such as type 2 diabetes. However, obesity is also associated with development of an autoimmune response against various organs, including pancreatic beta cells. The prevalence of such autoimmune processes in children and their possible contribution to the increased incidence of type 1 diabetes is currently unclear. Therefore, the present study assessed the prevalence of autoantibodies against pancreatic islet beta cell’s antigens in children and adolescents with simple obesity. Material and methods This prospective observational study included pediatric patients (up to 18 years of age) with simple obesity hospitalized between 2011 and 2016 at the Department of Pediatrics, Diabetology, Endocrinology and Nephrology of the Medical University of Lodz. Children with acute or chronic conditions that might additionally affect insulin resistance or glucose metabolism were excluded. Collected clinical data included sex, age, sexual maturity ratings (Tanner`s scale), body height and weight, waist and hip circumference, amount of body fat and lean body mass. Each participant underwent a 2-hour oral glucose tolerance test with simultaneous measurements of glycaemia and insulinemia at 0`, 60` and 120`. In addition, glycated hemoglobin HbA1c, fasting and stimulated c-peptide, total cholesterol, as well as high- and low-density cholesterol and triglycerides were measured. Insulin resistance was assessed by calculating HOMA-IR index. The following autoantibodies against pancreatic islet beta cells were determined in each child: ICA - antibodies against cytoplasmic antigens of pancreatic islets, GAD - antibodies against glutamic acid decarboxylase, ZnT8 - antibodies against zinc transporter, IA2 - antibodies against tyrosine phosphatase, IAA – antibodies against insulin. Results The study group included 161 children (57.4% boys, mean age 13.1 ± 2.9 years) with simple obesity (mean BMI z-score +2.2 ± 1.6). Among them, 28 (17.4%) were diagnosed with impaired glucose metabolism during OGTT [23 (82.2%) – isolated impaired glucose tolerance (IGT), 3 (10.7%) – isolated impaired fasting glucose (IFG), 2 (7.1%) – IFG and IGT]. Of the children tested, 28 (17.4%) were tested positive for at least one islet-specific autoantibody [with similar percentages in boys (15, 17.4%) and girls (13, 17.3%), p=0.9855], with ICA being the most common (positive in 18, 11.2%), followed by IAA (7, 4.3%), ZnT8 (5, 3.1%), GADA (3, 1.9%) and IA2 (1, 0.6%). There was no association between the presence of the tested antibodies and age, sex, stage of puberty, parameters assessing the degree of obesity, HbA1c, lipid levels and basal metabolic rate. However, autoantibody-positive subjects were more likely to present IFG or IGT in OGTT compared to those who tested completely negative (9, 32.1% vs 19, 14.3%, p=0.0280). Their HOMA-IR was also significantly higher (HOMA-IR: 4.3 ± 1.9 vs 3.4 ± 1.9, p=0.0203) and this difference remained statistically significant after adjusting for sex and age (p=0.0340). Conclusions Children and adolescents with simple obesity presented a higher prevalence of markers of autoimmune response against pancreatic beta cells than the general population. Most often, they had only one type of antibody - ICA. The presence of autoimmune response indicators against pancreatic islet antigens is more common in obese patients with impaired carbohydrate metabolism and is associated with lower insulin sensitivity.